Shingles with secondary asymptomatic CNS involvement!. (30th May 2012) - Ahmed, Syed Viqar; Hamada, Hazim; Jayawarna, Chaminda; Chandra, Sumit
Abstract : A 32-year-old married Asian woman, previously fit and well, presented with a 3-day history of interscapular back pain followed by a 1-day history of frontal headache and a few episodes of vomiting. She did not have photophobia or neck stiffness. On examination, there was evidence of herpes zoster infection involving the right T3 dermatome. There were no signs of meningeal irritation, cognitive impairment or any neurological deficit. As it is uncommon to have reactivation of herpes zoster infection at a young age, HIV serology was requested to exclude immunodeficiency state. While awaiting serology, a lumbar puncture was performed to exclude opportunistic infections of the central nervous system as she had transient headache and vomiting at the onset. The cerebrospinal fluid showed an elevated level of protein, an increase in lymphocytes and a strongly positive PCR for varicella zoster. The HIV test was negative. Oral acyclovir was changed to intravenous therapy and, a week later, she was discharged with uneventful recovery.